Omega-3 Fatty Acids for Dry Eye Disease: An Updated Systematic Review - Sari, Gusti Ayu Ning Wikan; Atnil, Daniel; Pelupessy, Thessia Eflien (Pusat Mata Nasional Rumah Sakit Mata Cicendo Bandung, 2025)
Introduction: Dry eye disease (DED) is a multifactorial disorder involving tear film instability and ocular surface inflammation. Oral omega-3 fatty acids have been investigated as adjunctive therapy due to their anti-inflammatory and tear-stabilizing effects. Methods: This systematic review followed PRISMA guidelines and included randomized controlled trials and prospective studies published up to August 2025. Databases searched were PubMed, Scopus, Web of Science, and the Cochrane Library. Primary outcomes were tear break-up time and patient-reported symptoms, with secondary outcomes including Schirmer test results, ocular surface staining, inflammatory markers, and adverse events. Results: Fifteen studies across various DED subtypes were included. Most reported improvements in tear film stability and symptoms, although two large trials found no significant benefit. Omega-3 supplementation was generally safe, with mild gastrointestinal effects. Conclusion: Oral omega-3 supplementation is safe and shows moderate efficacy as an adjunctive therapy for dry eye disease, particularly in patients with tear film instability and ocular surface inflammation. Variability in outcomes across studies highlights the need for standardized formulations, optimal dosing regimens, and subgroup-specific recommendations in future trials.